Implantação de uma Unidade Sentinela Centro de Referência em Medicina Internacional e de Viagem no Hospital das Clínicas da Universidade Federal de Goiás (HC / UFG) - AIRES, Leticia Mara Conceição (2010)
Introduction: The number of domestic and international travel has increased in past years. This way, Travel Medicine, has become an important subject, with the emergence of services that provide health care to travelers. Objective: To evaluate strategies used in deploying Sentinel Unit Reference Center for International and Travel Medicine at the HC / UFG. Methods: First approach: Systematic Review of Literature using the keywords: "Travel and medicine", "Travel and prevention", "Travel and Disease and Medicine" and "Traveler and medicine . Then were selected articles in English, Spanish and Portuguese, from 2004 to 2008. Second approach: a descriptive, qualitative and quantitative, with evaluation of actions taken during the period preceding the implementation of the Unit. Results: In the literature review were found 1,301 articles, and 72 included for analysis, we observed that malaria is the most studied disease, the main preventive measures discussed are chemoprophylaxis for malaria and vaccination. Health professionals working in Travel Medicine are general practitioners, pharmacists and nurses in various parts of the world, and among the obstacles we stress the lack of information in travelers, the lack of professional preparation and last-minute travelers. In a qualitative and quantitative research was performed a retrospective study in which differences were observed between physicians at the General Hospital and the tropical Diseases Hospital, where 1% of primary and 12.1% of the latter, asked about previous trips during office visits, and future study outlined profiles of health workers and travelers in their Knowledge, Attitudes and Practices in Travel Medicine, and noticed that 38% of professionals and travelers refer or seek treatment, although 91% of respondents consider it important to receive pre-departure orientation. Courses were held, symposium, lectures in education activities proposed. Travel Medicine now has code of regulation for public patients receive, and in 2009 and 2010 the Unit attended eight international travelers. Conclusions: The Travel Medicine faces many obstacles in Goiânia, as elsewhere in the world, being the main one the lack of information. We need a massive USCREMIVI disclosure to reach the objective of service to the traveler, in order of doing a situational diagnosis and to establish an educational facet.